A combination therapy for KRAS‐mutant lung cancer by targeting synthetic lethal partners of mutant KRAS. Issue 1 (28th October 2016) - Pang, Xiufeng; Liu, Mingyao
Abstract: The KRAS gene is frequently mutated in multiple cancer types, but it fell off the drug discovery radar for many years because of its inherent "undruggable" structure and undefined biological properties. As reported in the paper entitled "Suppression of KRas‐mutant cancer through the combined inhibition of KRAS with PLK1 and ROCK" in Nature Communications, we performed a synthetic lethal screening with a combinatorial strategy on a panel of clinical drugs; we found that combined inhibition of polo‐like kinase 1 and RhoA/Rho kinase markedly suppressed tumor growth in mice. An increase in the expression of the tumor suppressor P21 WAF1/CIP1 contributed to the synergistic mechanism of the combination therapy. These findings open a novel avenue for the treatment of KRAS ‐mutant lung cancer.